Cardiac magnetic resonance assessment of takotsubo cardiomyopathy. Issue 1 (January 2016) - Abbas, A.; Sonnex, E.; Pereira, R.S.; Coulden, R.A.
Abstract : Takotsubo cardiomyopathy is an important condition that can be difficult to differentiate from acute coronary syndrome on the basis of clinical, electrocardiogram, and cardiac enzyme assessment alone. Although coronary angiography remains important in the acute assessment of patients with suspected takotsubo cardiomyopathy, cardiac magnetic resonance (CMR) has emerged over the last decade as an important non-invasive imaging tool in the diagnosis and follow-up of this condition. We present a review highlighting the CMR features of takotsubo cardiomyopathy and its complications with particular focus on differentiating this condition from acute myocardial infarction and myocarditis.